Effect of Degree and Length of Slope and Soil Type on Plant Nutrient Losses by Water Erosion in the Alluvial Tracts of Uttar Pradesh - Goel, K.N.; Khanna, M.L.; Gupta, R.N. (Journal of Soil and Water Conservation, 2022)
Effect of Degree and Length of SlopeBesides the plant nutrients removed by crops, a considerable amount is lost from the soil by erosion through water or wind. Duley and Miller (1923), Lipman and Conybeare (1936) and Bobko (1943) during their studies on loss of nutrients by erosion observed that the losses are considerable and in some cases higher than the annual crop removal. Middleton et al. (1934) and Rogers (1941) found that the eroded material was richer than the original soil in respect of col)oidal clay and plant nutrients. Stallings (1951), Massey & Jackson (1952) and Stoltenberg and White (1953) found erosion to be a selective process which decreases soil fertility. Tamhane et al. (1959) while studying the effect of intensity of rainfall on the soil loss and runoff observed that the soil lost in the runoff is much more clayey as compared to original soil and clay and silt were the main mechanical constituents carried away by runoff water. Barrow & Kilmer (1963) have summarised the work done on plant nutrient losses by water erosion.and Soil Type on Plant Nutrient Losses by Water Erosion in the Alluvial Tracts of Uttar Pradesh